2014
DOI: 10.1002/marc.201400363
|View full text |Cite
|
Sign up to set email alerts
|

Breath Figures of Nanoscale Bricks: A Universal Method for Creating Hierarchic Porous Materials from Inorganic Nanoparticles Stabilized with Mussel‐Inspired Copolymers

Abstract: High-performance catalysts and photovoltaics are required for building an environmentally sustainable society. Because catalytic and photovoltaic reactions occur at the interfaces between reactants and surfaces, the chemical, physical, and structural properties of interfaces have been the focus of much research. To improve the performance of these materials further, inorganic porous materials with hierarchic porous architectures have been fabricated. The breath figure technique allows preparing porous films by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…In another study, Han et al prepared elliptical pores with dodecanethiol-capped gold NPs by carefully controlling the direction and velocity of the airflow. 348 Other NPs have also been used to prepare BFAs, such as various metal oxide NPs, 349 340 They found that optimum surfactants were C n H 2n+1 NH 4 Br (n = 12−14) for SiO 2 , C n H 2n+1 COOH (n = 7− 11) for TiO 2 and Co, and C n H 2n+1 SH (n = 10−12) for CdS. The C 11 H 23 COOH/TiO 2 -based films maintained their honeycomb morphologies after calcination at 500°C, and they exhibited higher photocatalytic activity than the calcinated nonporous films.…”
Section: Nonpolymeric Materialsmentioning
confidence: 99%
“…In another study, Han et al prepared elliptical pores with dodecanethiol-capped gold NPs by carefully controlling the direction and velocity of the airflow. 348 Other NPs have also been used to prepare BFAs, such as various metal oxide NPs, 349 340 They found that optimum surfactants were C n H 2n+1 NH 4 Br (n = 12−14) for SiO 2 , C n H 2n+1 COOH (n = 7− 11) for TiO 2 and Co, and C n H 2n+1 SH (n = 10−12) for CdS. The C 11 H 23 COOH/TiO 2 -based films maintained their honeycomb morphologies after calcination at 500°C, and they exhibited higher photocatalytic activity than the calcinated nonporous films.…”
Section: Nonpolymeric Materialsmentioning
confidence: 99%
“…[9][10][11][12] Various kinds of catechol-containing polymers possessing adhesion and reduction properties have been reported. 4,[13][14][15][16][17][18] However, due to their reactivity to a wide variety of functional groups, there have only been a few reports on the formation of block and sequence controlled copolymers containing catechol groups, 19 which requires propagation reactions without side reactions in order to achieve living polymerization conditions. We rst reported the synthesis of poly(vinyl catechol-blockstyrene) (PVCa-b-PSt) diblock copolymers by using the reversible-addition fragmentation transfer (RAFT) polymerization of 3,4-dimethoxystyrene (DMSt) and styrene (St) followed by deprotection of the methoxy groups by BBr 3 treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported the formation of honeycomb films from metal oxide nanoparticles, which can be used for fuel cells stabilized with lipids [46]. Saito et al reported that dispersions of inorganic nanoparticles stabilized with amphiphilic copolymers containing catechol groups could be used to form inorganic hierarchic porous films [47,48] (Figure 6). When TiO 2 and other oxide nanoparticles with diameters on a scale of tens of nanometers were stabilized with an amphiphilic copolymer, they dispersed as secondary aggregates.…”
Section: Nanoparticles and Low-dimensional Materialsmentioning
confidence: 99%
“…anisotropic small ZnO (short rods), and (w)-(z) anisotropic large ZnO nanoparticles (long rods) before and after heating at 600°C in air. Reproduced with permission from [47,48] (Copyright 2013, Wiley).…”
Section: Solventmentioning
confidence: 99%